(untitled) (Revista de Ciências Agroveterinárias, 2012)
The brown spot is a common and one of the main diseases of barley (Hordeum vulgare) in the Southern Brazilian crops. The use of fungicide when the disease reaches around 20% of incidence (I) and/or 2% of severity (S) is one of the most efficient and indicated strategies to control the disease, according to the Technical Culture Indication (TCI). Linear equations to predict severity based on leaf brown spot incidence were obtained for the BRS Cauê cultivar which was recently recommended by TCI. The brown spot intensity values were obtained from economic damage threshold (EDT) fi eld experiments carried out in Muitos Capões/RS municipality in the South of Brazil during 2009 and 2010 growing seasons. The disease intensity gradient experiments followed a completely randomized design with nine treatments and four replications. The leaf incidence and severity were quantified in ten random tillers per parcel in the growing stages: beginning of tillering (EC22), end of tillering (EC39) and head emergence (EC56) and the data were submitted to regression analysis. The results showed that leaf severity can be estimated based on leaf incidence and 20% of leaf incidence corresponds to a leaf severity 20 to 30 times less than the 2% indicated by TCI. Therefore, the action threshold indication based on 20% of leaf incidence is too high to begin the chemical control.